Granting Sensorial Properties to Metal Parts through Friction Stir Processing - Ferreira, Pedro M. (2023)
The authors would like also to thank to Micronsense-Metrologia Industrial (Leiria, Portugal) for the μCT analysis. The authors would also like to thank Prof. Catarina Santos for granting access to the MicroLab - Electron Microscopy Laboratory (Instituto Superior Técnico) for the SEM analyses.